Prenatal diagnosis and management of fetal lung malformation - Villamonte, Wilfredo (2015)
The cystic adenomatous malformation (CAM) is a rare fetal lung lesion. Its frequency is about 1 in 4000 births and is characterized by an overgrowth of terminal respiratory bronchioles that form cysts of various sizes. It can be associated with polyhydramnios and pulmonary hypoplasia. We describe here a case of prenatal diagnosis and management of CAM at 3400 m (Cusco).